PHYSICOCHEMICAL, MECHANICAL, AND SENSORY CHARACTERISTICS OF EDIBLE PALM STARCH BUTYRATE PHOSPHATE FILMS AT DIFFERENT CONCENTRATIONS - Rahim, Abdul; Nurmi; If'all (Universitas Veteran Bangun Nusantara, 2025)
This study objectives to obtain the concentration of phosphorylated butyrylated arenga starches (PBAS) at different concentrations in the manufacture of edible films based on the physicochemical, mechanical and sensory characteristics of the edible film produced. The research was conducted at the Agroindustry Laboratory, Faculty of Agriculture, Tadulako University, Palu. The study design used a completely randomized design (CRD) and a randomized block design (RBD). CRD was used to determine the effect of PBAS edible film at different concentrations on physicochemical characteristics including thickness, water holding capacity (WHC), oil holding capacity (OHC), water vapor transmission rate (WVTR), solubility and expandability, water content, pH test, and mechanical characteristics include tensile strength, elongation and Young's modulus. RBD was used to determine the effect of PBAS edible film at different concentrations on the sensory properties of edible film, namely color, texture, aroma and overall. The treatment used consisted of 8 levels, namely 2,0; 2,5; 3,0; 3,5; 4,0; 4,5; 50 and 5,5% were repeated 2 times to obtain 16 experimental units. The results showed that the optimal concentration of PBAS was 3,0%. Thickness, solubility, moisture content, WVTR, tensile strength, and elongation increased with increasing concentration of PBAS, while WHC, OHC, swelling power, pH, and modulus young's decreased with increasing concentration of PBAS. The sensory of edible film in the form of color, texture, aroma, and overall were included in the like category. The resulting edible film has good potential to be applied in food products.